Amplifying effects of recurrent drought on the dynamics of tree growth and water use in a subalpine forest. (27th June 2022) - Oberleitner, Florian; Hartmann, Henrik; Hasibeder, Roland; Huang, Jianbei; Losso, Adriano; Mayr, Stefan; Oberhuber, Walter; Wieser, Gerhard; Bahn, Michael
Abstract: Despite recent advances in our understanding of drought impacts on tree functioning, we lack knowledge about the dynamic responses of mature trees to recurrent drought stress. At a subalpine forest site, we assessed the effects of three years of recurrent experimental summer drought on tree growth and water relations of Larix decidua Mill. and Picea abies (L. Karst.), two common European conifers representative for contrasting water‐use strategies. We combined dendrometer and xylem sap flow measurements with analyses of xylem anatomy and non‐structural carbohydrates and their carbon‐isotope composition. Recurrent drought increased the effects of soil moisture limitation on growth and xylogenesis, and to a lesser extent on xylem sap flow. P. abies showed stronger growth responses to recurrent drought, reduced starch concentrations in branches and increased water‐use efficiency when compared to L. decidua . Despite comparatively larger maximum tree water deficits than in P. abies, xylem formation of L. decidua was less affected by drought, suggesting a stronger capacity of rehydration or lower cambial turgor thresholds for growth. Our study shows that recurrent drought progressively increases impacts on mature trees of both species, which suggests that in a future climate increasing drought frequency could impose strong legacies on carbon and water dynamics of treeline species.